The Effect of Wall Shooting Exercise Using the Beef Concept on Free Throw Shooting Accuracy in High School Women Students - Enna Angela M (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. This research was motivated by the results of the free throw performed by the women's basketball extracurricular which was not optimal and not appropriate in its implementation. free throw is the accuracy of the direction of the ball shot towards the ring, where this shot is taken from behind the free throw line in a basketball game. Materials and methods. Methods This research uses an experimental method with One Group, namely Pre-test and Post-test Design. The data collection technique was saturated sampling with inclusion and exclusion criteria. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. Results. Data analysis in this study used the Wilcoxon test, Paired Sample T-test. Research results based on the statistical output